Gross Morphometrical Study on the Atypical (6th and 7th) Cervical Vertebrae of Blue bull (Boselaphus tragocamelus) with Special Reference to Sexual Dimorphism - Sathapathy, Srinivas; Dhote, Balwinder Singh; Mahanta, Dwipjyoti; Selvaraju, Tamilselvan; Mrigesh, Meena (International Journal of Livestock Research, 2018)
The present study was carried out on the atypical cervical vertebrae, especially sixth (C6) and seventh (C7) cervical vertebrae of six specimens of adult Blue bull (Boselaphus tragocamelus) of either sex after collection of macerated bones. It was found that these vertebrae were comprised of body, arch and processes. The arch had laminae and pedicles. The processes were dorsal supraspinous, transverse, cranial and caudal articular processes. The ventral division of transverse process of C6 was quadrilateral plate like. The transverse foramina were absent in C7 and also the transverse process was single in C7. There was a pair of costal facets one on either side of caudal surface of body of C7. The supraspinous process of C7 was very well developed and almost resembled with that of the thoracic vertebrae. Biometrical observations on different parameters of C6 and C7 reflected significance (P<0.05) differences between the sexes of this species which would help the wild life Veterinarians in identification of species and differentiation of sex in this animal.